Penguatan Perilaku Ekologis Berbasis Komunitas melalui Edukasi Digital pada Kawasan Taman UMKM Desa Ngadirejo - Surayanah; Lilik Bintartik; M. Anas Thohir; Dina Nur Abidah; Dhiya Nasywa; Najin Fadila Foresta (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
High levels of economic activity in the Kedhung Town Square MSME Park area (Ngadirejo Village, Trenggalek Regency) have led to environmental issues, including increased single-use plastic consumption, poor waste sorting practices, and suboptimal eco-friendly behavior among the community. This Community Service (PKM) initiative aims to strengthen community-based eco-friendly behavior by leveraging digital education for MSME operators, area managers, and the general public. The methods employed included outreach sessions, lectures, discussions, hands-on practice, and mentoring on the creation of social media-based environmental educational content. Program effectiveness was evaluated using pre-tests, post-tests, and participant response questionnaires. Results showed an improvement in participant understanding, evidenced by the rise in average scores from 84.77 in the pre-test to 91.69 in the post-test. Furthermore, participants successfully produced digital posters, short videos, and visual content for environmental campaigns and demonstrated active participation in eco-friendly practices—such as reducing single-use plastics, sorting waste, and using social media for environmental education. This program has positively impacted community awareness and participation in community-based environmental management and holds potential as a model for community empowerment through digital education. Thus, digital education has proven to be an effective approach in fostering collective eco-friendly behavior, paving the way for a clean, healthy, and sustainable MSME area.